The organizational and legal mechanisms of interaction between public administration bodies and businesses under martial law conditions - Grynchuk Nataliіa; Zalizniuk, Viktoriia; Tyshko, Dmytro; Noskov, Oleksii; Maksymovych, Roman (Edelweiss Applied Science and Technology, 2024)
Business, authorities, and the public are interconnected, so effective mechanisms for their cooperation are necessary, especially in times of economic crisis. Under the conditions of martial law, when economic crisis is combined with security, loss of resources, property and disruption of logistics, the importance of mutually beneficial relations between business, government and the population increase. Our research is devoted to determining the mechanisms of interaction between business and authorities and evaluating their effectiveness. The factors of cooperation between economic entities were analyzed and, based on the analysis of the recovery program of the Kyiv region, the effectiveness of measures aimed at overcoming the crisis related to the war was determined. The positive impact of decentralization for the rapid recovery of the de-occupied region was determined, which was manifested in the priority provision of demining territories and construction of shelters, restoration of life support facilities and infrastructure in more than 70% of cases, planning the creation of economic clusters based on industrial parks with the formation of more than 17000 jobs. The effectiveness of the applied methods is confirmed by a high rate of relocation of enterprises to the region even shortly after the reoccupation. Our study found that despite the difficult conditions of administration, the strategy of business-government interaction includes the principles of sustainable development, which corresponds to the modern trends of conducting business in countries with developed economies.